Dawn to Dusk: Diurnal Rhythm of the Immune Response in Rainbow Trout (Oncorhynchus Mykiss) - Montero, Ruth (Biology (Basel), 2019)
The daily change of light and dark periods influences different physiological processes including feeding, resting and locomotor activity. Previously, several studies on mammalian models revealed a strong link between day-night rhythms and key immunological parameters. Since teleost fishes possess innate and adaptive immune responses like those observed in higher vertebrates, we aimed to elucidate how changes in light-dark cycles shape the immune system of fish. Using the rainbow trout laboratory model, we investigated the link between diurnal rhythms and immune competence of fish. Initially, the cell composition and phagocytic activity of leukocytes was analyzed in the circulation as well as in the head kidney, the functional ortholog of mammalian bone marrow. Once the baseline was established, we evaluated the ability of fish to respond to a bacterial stimulus, as well as the changes in antimicrobial activity of the serum. Our results suggest increased immune competence during the day, manifested by the higher presence of myeloid cells in the circulation; increased overall phagocytic activity; and higher capacity of the sera to inhibit the growth of Aeromonas salmonicida. Notably, our flow cytometric analysis identified the myeloid cells as the major population influenced by the time of day, whereas IgM(+) B cells and thrombocytes did not vary in a significant manner. Interestingly, the presence of myeloid cells in blood and head kidney followed complementary trends. Thus, while we observed the highest number of myeloid cells in the blood during early morning, we witnessed a reverse trend in the head kidney, suggesting a homing of myeloid cells to reservoir niches with the onset of the dark phase. Further, the presence of myeloid cells was mirrored in the expression of the proinflammatory marker tnfa as well as in the number of leukocytes recruited to the peritoneal cavity in the peritonitis model of inflammation. Overall, the data suggest a connection between diurnal rhythms and the immune response of rainbow trout and highlight the relevance of rhythmicity and its influence on experimental work in the field of fish chronoimmunology.